Solid-phase manganese concentrations of surface sediments from sediment core SO268/2_106-1 (MUC-22) during SONNE cruise SO268/2, central Pacific - Sophie Anna Luise Paul; Andrea Koschinsky (PANGAEA, 2022)
Surface sediments from the Clarion Clipperton Zone, central Pacific were analyzed for solid-phase Mn to assess potential Mn mobilization into the pore water from the solid phase during early diagenesis. Samples were taken during the SO268 cruise to the German and Belgian license areas for polymetallic nodule mining in the Clarion Clipperton Fracture Zone as part of the MiningImpact project. Sediment cores were collected with multicorers (MUC) and ROV push cores (PUC). Pore water was extracted by means of centrifugation prior to analyses of the sediments. Samples were freeze-dried and acid pressure digested using HF and HClO4. Manganese was then analyzed in the digestion solutions with an inductively coupled plasma optical emission spectrometer.
In: Paul, Sophie Anna Luise; Schmidt, Katja; Achterberg, Eric Pieter; Koschinsky, Andrea (2024): Pore-water and solid-phase trace metals from sediment cores during SONNE cruises SO268/1 and SO268/2, central Pacific [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.965035